Polar Machine Maintenance: Pemeliharaan Mesin Polar - Mahendra, Surya; Ahfas, Akhmad (Universitas Muhammadiyah Sidoarjo, 2024)
Polar Mohr machines are a well-known brand in the printing industry known for its quality paper cutting machines and printing materials. The method used is descriptive research method focused on the problem. The discussion of the polar mohr machine is starting from the position button, length button, reverse button, forward button, reset button and start button. The results of the mohr polar machine are from the polar machine planning to PLC assembly and installation. The conclusion of the polar machine is very helpful for smooth running in the industrial world because it simplifies the process of cutting paper. One of the characteristics of the Polar Mohr machine is its ability to make the cuts we want.Keywords – polar mohr; paper machine panels; panel wiring